An Unknown Belt Buckle (1732) of Hieromonk Isaiah from Ioannina from a Private Collection in Greece - Trifonova, Alexandra Ph. (Actual Problems of Theory and History of Art, 2023)
The article presents an unknown belt buckle (22,5×9,5 cm) from a private collection in Attica, Greece. It is made of silver and copper alloy, gilded for the most part, and consists of three parts — a central oval shaped part with the New Testament Holy Trinity, and two side parts with the Annunciation, surrounded by two prophets, David and Solomon. The top side of the belt buckle bears a dedicatory inscription in Greek: ΔΙΑ CHΝΔΡΟΜΗC· ΕΜΟΥ · ΙCΑ/IΟΥ ΙΕΡΟΜΟΝΑΧΟΥ · ΤΟΥ / ΕΞ ΙΩΑΝΗΝΩΝ 1732 ΕΚΑΤΑC/ΚΙΑCΘI ΕΙC ΜΕΛΕΝHΚΟΝ (With the contribution of me, hieromonk Isaiah from Ioannina, 1732, made in Melenikon), whereas the back side bears another inscription: ΔΟΥΛΟC ΤΟΥ ΘΕΟY / ΔΝΜIΤΡΙΟC (Servant of God Dimitrios). The object belongs to the group of hieratical (ecclesiastical) belt buckles. It is a very interesting and important artifact for the study of post-Byzantine silverware production, because it bears the name of a person from the ecclesiastical circle, Hieromonk Isaiah of Ioannina, who commissioned it, the name of the town where the belt buckle was made, Melenikon (Melnik), and also the year in which it was made — 1732. Moreover, the belt buckle bears the name of the servant of God Demetrios, who probably was its maker or someone who owned it later. The form, as well as the depictions of the New Testament Holy Trinity and the Annunciation with the prophets David and Solomon, demonstrate some new stylistics trends and new subjects in decoration of hieratical belt buckles so far unknown.
Keywords: Post-Byzantine art; belt buckle; Ioannina; Melnik; hieromonk Isaiah; Dimitrios